FRI0266 Long-Term Efficacy and Tolerability of Mycophenolate Mofetil Therapy in Diffuse Scleroderma Skin Disease. (15th July 2016) - Boulos, D.; Rajadurai, A.; Ngian, G.S.; Elford, K.; Stevens, W.; Proudman, S.; Roddy, J.; Nikpour, M.; Youssef, P.; Hill, C.; Sahhar, J.
Abstract : Background: Skin involvement in diffuse systemic sclerosis (dSSc) is progressive and can be extremely debilitating, however, treatment options remain limited. Although many disease modifying agents have been examined in dSSc, only cyclophosphamide has randomised controlled data suggesting efficacy in the treatment of skin thickening. 1 Several observational studies suggest benefit in skin disease with mycophenolate mofetil (MMF) therapy; 2 which, given its more favourable side effect profile, would be a preferable alternative to cyclophosphamide. Objectives: To assess the long-term efficacy and tolerability of MMF in patients with dSSc in the Australian Scleroderma Cohort Study. Methods: The Australian Scleroderma Cohort Study is a longitudinal study of disease outcomes in patients with SSc. Patients with dSSc and baseline modified Rodnan skin score (mRSS) ≥12 who were treated for a minimum twelve months with MMF for the primary indication of skin disease were included, and their prospectively collected data were retrieved. The proportion with clinically significant improvement in skin scores (defined as reduction in mRSS≥4 from baseline) and stable disease (change in mRSS <4) were compared to those with clinical deterioration (increase in mRSS≥4) as well as adverse effects resultant of therapy. Results: 74 participants were identified and of these, 44 met inclusion criteria. The mean age of participants was 53±12 years and 36 (82%) were female. The mean duration of disease at MMF commencement was 4.9±4.3 years, with 23 participants (52%) commencing MMF within 2.5 years. The mean duration of therapy was 2.7±1.7 years. The mean mRSS at baseline was 25.3 with a reduction of 3.7 (p-value <0.01) after one year of therapy and a mean total reduction in mRSS of 8.0 (p-value <0.01). Response to treatment was not affected by disease duration at onset of MMF therapy as expected. Over the first year of therapy, 24 participants (48%) demonstrated clinically significant improvement in skin scores, increasing to 92% clinically improved after four years of therapy. MMF was well tolerated, with two participants (5%) ceasing the drug due to adverse effects. Conclusions: MMF was associated with improved skin scores and was well tolerated in the treatment of dSSc. Given the natural history of dSSc where skin involvement can spontaneously improve, placebo-controlled studies are required to confirm whether improvement can be attributed to MMF therapy. References: Tashkin DP, Elashoff R, Clements PJ, Goldin J, Roth MD, Furst DE et al. Cyclophosphamide versus Placebo in Scleroderma Lung Disease. NEJM. 2006; 354(25):2655–66. Mendoza FA, Nagle SJ, Lee JB, Jimenez SA. prospective observational study of mycophenolate mofetil treatment in progressive diffuse cutaneous systemic sclerosis of recent onset. Ann Rheum Dis. 2012; 39(6):1241–7. Disclosure of Interest: None declared